Large tetrapod burrows from the Middle Triassic of Argentina: A behavioural adaptation to seasonal semi-arid climate? - Krapovickas, Verónica (2013)
We report the discovery of large burrow casts in the early Middle Triassic Tarjados Formation, at Talampaya National Park, north-western Argentina. Facies analysis indicates the burrows are preserved in sandbars deposited by an ephemeral river under semi-arid and seasonal climatic conditions. The structures are mostly preserved in longitudinal cross-section and consist of an opening, an inclined tunnel (ramp), and a terminal chamber. The ramp is 8-14cm in height, up to 130cm in length and penetrates 49-63cm bellow the palaeosurface with an inclination of 22°-30°. We studied burrow cast dimensions, overall architectural morphology, surficial marks, and compared them with other large burrows of both invertebrate and vertebrate origin. A tetrapod origin of the burrow casts was established based on: distinctive architecture, and size, which is more than twice the most common size range for large terrestrial invertebrate burrows. Comparison with other Upper Permian and Triassic tetrapod burrows allows us to identify three general morphological groups: (1) simple inclined burrows; (2) helical burrows; and (3) burrow network complexes, representing different behaviours. A study of tetrapod body fossils preserved within other Upper Permian and Triassic burrows shows that the Tarjados structures were most likely produced by non-mammalian cynodonts. The environmental and climatic context suggests that aridity and seasonality played a fundamental role selecting burrowing behaviour in therapsids and that by the Early-Middle Triassic their burrowing behaviour attained a complexity comparable to modern mammals. □Argentina, behaviour, palaeoclimate, Permo-Triassic, Tarjados Formation, Tetrapod burrows.